Improved Magnetic Behavior Of Hemicycle PM Motor Via Stator Modification - Mohd Jamil, Mohd Luqman; Tan, Cheng Kwang; Jidin, Auzani (Institute Of Advanced Engineering And Science (IAES), 2020)
This article investigates electromagnetic performance of a hemicycle PM motor by introducing a little modification on both ends of a hemicycle stator. Prior to the investigation, an analytical model for the hemicycle PM motor weight is derived analytically for the purpose of comparison with a conventional design. Both motor weights are then verified and the hemicycle motor is found to have lighter weight than the conventional design. By having a proper design modification, an optimum motor performance is achievable due to improved magnetic permeance. Two designs that have different arc angle; i) 180° (188.5 mm arc length) and ii) >180° (204.2 mm arc length) are the subjects of investigation. It is found that a hemicycle PM motor in which arc angle >180° results maximum torque average with the smallest torque ripple and smallest cogging torque